Global Trade in the Emerging Business Environment - Mohiuddin, Muhammad; Wang, Jingbin; Samim Al Azad, Md; Ahmed, Selim (IntechOpen, 2022)
Global Trade in the Emerging Business Environment explores global trade dynamics in the emerging business environment. Globalization, technological advancements, Industry 4.0, China's Belt and Road Initiative, and the COVID-19 pandemic are changing the global trade ecosystem. Companies and countries need to evaluate these rapid changes and adjust their respective business strategies and policy formulations. This book discusses such strategies and how firms and countries can reposition themselves within the current environment.